Tipologi Kejahatan Siber dan Penanggulangannya di Indonesia: Klasifikasi, Modus Operandi, dan Evaluasi Kerangka Hukum dalam Menghadapi Ancaman Digital Kontemporer - Gilang Rizki Aji Putra (UIN Jakarta, 2023)
Abstract: Cybercrime has evolved from simple hacking into a multidimensional, organized criminal industry operating across jurisdictions. This article aims to classify the typology of cybercrime in Indonesia, analyze emerging modus operandi, and evaluate the effectiveness of existing legal and institutional frameworks in addressing these threats. Using a normative legal research method with typological, statutory, and case study approaches, the study identifies seven major categories of cybercrime in Indonesia, each with distinct technical characteristics and social impacts. The findings reveal that the national regulatory framework remains sectoral and reactive, failing to anticipate crime hybridization and the use of anonymization technologies such as cryptocurrency and the dark web. Case analyses of online fraud, ransomware, and online child sexual exploitation demonstrate a gap between law enforcement capacity and offender sophistication. The study concludes that combating cybercrime requires multidimensional strategies integrating digital forensics, international cooperation, and platform regulation. Keywords: Cybercrime, Typology, Electronic Information and Transactions Law (ITE Law), Law Enforcement, Digital Forensics.